Argatroban pharmacokinetics and pharmacodynamics in critically ill cardiac surgical patients with suspected heparin-induced thrombocytopenia - Keyl, Cornelius; Zimmer, Emanuel; Bek, Martin Johannes; Wiessner, Michael; Trenk, Dietmar (Thrombosis and Haemostasis, 2016)
Only limited data are available on the pharmacokinetic and pharmacodynamic properties of argatroban in critically ill patients under clinical conditions. We determined plasma concentrations of argatroban, and its main metabolite M1, within a time period of 48 hours in 25 critically ill cardiac surgical patients, who were suspected of heparininduced thrombocytopenia and had the clinical need for anticoagulation. Argatroban infusion was started at 0.5 µg/kg/minute, and adjusted in 0.1–0.25 µg/kg/minute increments when the activated partial thromboplastin time (aPTT) was not within the target range. Median argatroban plasma half-life was 2.7 hours (interquartile range 1.8 to 7.3). Linear regression analysis revealed that argatroban half-life was significantly related to the total bilirubin concentration (R2 = 0.66, p< 0.001), as well as to the metabolism of argatroban, which was assessed by the ratio of the areas under the concentration time curves (AUC) of argatroban and M1 (R2 = 0.60, p< 0.001). Continuous veno-venous haemodialysis did not significantly affect argatroban plasma half-life. The predictive property of argatroban plasma levels for aPTT was low (R2 = 0.28, p< 0.001). Multiple linear regression analysis revealed significant contributions of age and serum albumin levels to the effect of argatroban on aPTT, expressed as the AUC ratio argatroban/aPTT (R2 = 0.67, adjusted R2 = 0.65, p< 0.001). In conclusion, argatroban plasma half-life is markedly increased in critically ill cardiac surgical patients, and further prolonged by hepatic dysfunction due to impaired metabolism. Patient age and serum albumin concentration significantly contribute to the variability in the anticoagulant activity of argatroban.
Keywords: Argatroban; liver failure; haemodialysis; intensive care